“You can't even ask a question about your child”: Examining experiences of parents or caregivers during hospitalization of their sick young children in Kenya: A qualitative study - Okondo, Chantalle; Ndwiga, Charity; Sripad, Pooja; Abuya, Timothy; Warren, Charlotte E. (Frontiers in Health Services, 2022)
Background Globally, about 5.2 million children under the age of five died in 2019, and more than half of those deaths occurred in Sub-Saharan Africa. In almost every death of a sick child, there is a parent/caregiver seeking health services for their child. This study sought to understand the experiences of care for parents/caregivers (caregivers) as they navigate the hospital system with the aim of identifying opportunities to improve service delivery and child health outcomes. Methods Qualitative data were collected from five hospitals in Kenya: three in Nairobi County and two in Bungoma County. Twenty-five in-depth interviews with caregivers (couples and single women) of young children 0–24 months old, 17 focus group discussions with women and men, and 64 institutional ethnographic observations were completed. Data were analyzed by initial annotation of transcripts and field materials, followed by open coding and thematic analysis using Nvivo 12 software. Summary themes were used to compare experiences between female and male caregivers, their child's age group, and study sites. Results Caregivers faced complex processes of care while seeking health services for their sick young children. Three overarching themes emerged with some variability across female and male caregiver perspectives: (1) Navigating structural issues: long wait times, confusing payment mechanisms, overcrowding, unhygienic conditions, and strict visitation policies; (2) Interactions with providers: positive experiences, including providers showing empathy and concern, and negative experiences of harsh language, neglect, lack of privacy, discounting caregiver perspectives, and not involving men; Limited communication between caregivers and providers on child's diagnosis, treatment, and progress and lack of communication specifically between male caregivers and providers; and (3) Limited emotional support for both caregivers during difficult diagnosis or bereavement. Conclusions To improve experiences, interventions, programs, and policies need to focus on good provider-caregiver partnerships; enhancing opportunities for male engagement, such as supportive visiting hours; effective communication between caregivers and providers; access to adequate emotional support; and an enabling hospital environment.